Photo‐Thermal Approaches on Polyimide Film for Demonstration of Sub‐50 µm Polymer Stencil Mask - Bon‐Jae Koo; Jin‐Hyeong Lee; Hyo‐Kyung Kwon; Hwidon Lee; Joonsoo Jeong; Suk‐Kyun Ahn; Min‐Ho Seo (Advanced Electronic Materials)
Abstract Stencil masks are widely utilized in traditional macro‐scale patterning due to their simplicity and versatility in enabling various types of patterns. Compared to photoresist‐based methods, stencil‐based patterning enables chemical‐free processing and curved surface application. However, their application to micro‐scale patterning is constrained by challenges including precise fabrication, mechanical stability, and high production costs. Herein, a cost‐ and time‐effective, single‐step UV laser process is presented for fabricating polyimide stencil masks with micrometer‐resolution (down to 42.4 µm feature sizes) by optimizing photothermal effects on material. Specifically, the processing conditions are systematically explored and optimized to enable efficient etching of polyimide with a UV laser while maintaining its structural stability in a glassy state. This approach successfully yielded micro‐patterns with feature sizes below 50 µm on polyimide film. The developed method demonstrated high reproducibility, scalability, and stability, allowing polyimide films of varying thicknesses to be processed into stencil masks with dimensions down to 42.4 µm. Furthermore, the produced masks enable the formation of various micro‐patterns, including polygonal shapes and linear features, with high aspect ratios (<1:235.8) (42.4 µm width, 10 mm length). To demonstrate the practicality of this technology, wearable motion sensors are fabricated using stencil masks and successfully applied to advanced human‐machine interaction.